Effects of Simulated Microgravity on the Proteome and Secretome of the Polyextremotolerant Black Fungus Knufia chersonesos - Tesei, Donatella; Chiang, Abby J.; Kalkum, Markus; Stajich, Jason E.; Mohan, Ganesh Babu Malli; Sterflinger, Katja; Venkateswaran, Kasthuri (Frontiers in Genetics, 2021)
Black fungi are a group of melanotic microfungi characterized by remarkable polyextremotolerance. Due to a broad ecological plasticity and adaptations at the cellular level, it is predicted that they may survive in a variety of extreme environments, including harsh niches on Earth and Mars, and in outer space. However, the molecular mechanisms aiding survival, especially in space, are yet to be fully elucidated. Based on these premises, the rock-inhabiting black fungus Knufia chersonesos (Wt) and its non-melanized mutant (Mut) were exposed to simulated microgravity—one of the prevalent features characterizing space conditions—by growing the cultures in high-aspect-ratio vessels (HARVs). Qualitative and quantitative proteomic analyses were performed on the mycelia and supernatant of culture medium (secretome) to assess alterations in cell physiology in response to low-shear simulated microgravity (LSSMG) and to ultimately evaluate the role of cell-wall melanization in stress survival. Differential expression was observed for proteins involved in carbohydrate and lipid metabolic processes, transport, and ribosome biogenesis and translation via ribosomal translational machinery. However, no evidence of significant activation of stress components or starvation response was detected, except for the scytalone dehydratase, enzyme involved in the synthesis of dihydroxynaphthalene (DNH) melanin, which was found to be up-regulated in the secretome of the wild type and down-regulated in the mutant. Differences in protein modulation were observed between K. chersonesos Wt and Mut, with several proteins being down-regulated under LSSMG in the Mut when compared to the Wt. Lastly, no major morphological alterations were observed following exposure to LSSMG. Similarly, the strains’ survivability was not negatively affected. This study is the first to characterize the response to simulated microgravity in black fungi, which might have implications on future astrobiological missions.